Division of labor and satisfaction in preschool childrearing a household responsibility in Pattani, Thailand - Tanskul, Urai; Orlina, Elsa A. (1997., 1997)
The purpose of this study was to examine the effects of the family's macro-environment and micro-environment on the division of labor in preschool child-rearing and satisfaction in child care. The macro-environment included the following selected variables: religion, gender role attitudes and attitudes towards parenting and child-rearing; and the micro-environment included the following: family type, family income, educational attainment, and time allocation to child care. Data were obtained from 60 Buddhist and 90 Muslim couples who had at least one child ages ranging from four to six years old and residing in Muang municipality, Pattani, Thailand. Interview and participant observation were employed in gathering the data. Wilcoxon 2 sample test and Kruskal-Wallis test were used in data analysis. The findings indicated that Muslim couples expressed stronger attachment to traditional gender role attitudes than their Buddhist counterparts. They also reported higher degree of attitudes towards parenting and child-rearing compared to the Buddhist couples. Though wives still performed main functions in fostering the child's total development, there was a trend of egalitarian roles in activities pertaining to the child's emotional and social development. Husbands were likely to rate themselves sharing more in most of the activities. The following factors were found to have a positive effect on egalitarian division of labor in preschool child-rearing; being a Buddhist, having sensitive gender role attitudes, having higher degree of attitudes towards parenting and child-rearing, being a member of dual income family, and investing less time contribution in child care. Family income showed some positive effects on the couples' shared roles in the physical aspect of child development. In terms of satisfaction in preschool child-rearing, husbands perceived higher degrees of satisfaction. Factors that had positive effects on the satisfaction in child care are the following: having higher degree of attitudes towards parenting and child-rearing, being a member of single income family, belonging to the upper income bracket, and investing more time contribution in child care. Religion and gender role attitudes showed minimal influences on the satisfaction. Family types in terms of nuclear and extended families effected neither division of labor nor satisfaction in preschool child-rearing. This study did not reveal a clear picture of the effects of educational attainment on division of labor and satisfaction in preschool child-rearing. Qualitative information about values and beliefs concerning child-rearing were grouped into seven topics: religion, animism, economics, education, health, family planning, and parental roles. Some weaknesses of wives such as inconsistent temperament and less awareness of the child's food habits and bodily cleanliness were raised by the husbands. The wives, in turn, wished their husbands to tolerate the unstable emotion of the young child as well as to engage more in child care and other household tasks.
Computer print-out.
Thesis (Ph. D. Home Economics)--University of the Philippines, Diliman.
Keywords: Child rearing -- Thailand; Child care -- Thailand; Division of labor -- Thailand; Parenting; Women in development -- Thailand; Women -- Asia